2014
DOI: 10.1590/s1516-635x2014000100007
|View full text |Cite
|
Sign up to set email alerts
|

Digestible lysine requirements of broilers

Abstract: Modern broilers have been submitted to continuous genetic improvement, and therefore, their nutritional requirements must be constantly updated to ensure their performance. Two experiments were carried out to evaluate different digestible lysine levels for starter (10-21 days) and grower (22-35 days) phases. The experiments were carried out with male and female Cobb 500 broilers, distributed according to a randomized block experimental design in a 5x2 factorial arrangement (5 increasing digestible lysine level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
7
1
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 7 publications
7
7
1
15
Order By: Relevance
“…In this period, an interaction (p<0.05) between factors (sex and diet) was observed in the feed intake (Table 4), with males consuming diets in greater proportion (around 9.3% more) than females. Similar results were reported by Costa et al (2001); Mendes et al (2004); Sabino et al (2004); Kolling et al (2005); Lima et al (2008); Bernal et al (2014) and Tavernari et al (2014), who, when evaluating diets with different levels of crude protein, energy and amino acids in the finisher phase, observed differences regarding sex, in which male broilers showed best performance. FI (g)-Feed intake; BW (g)-Body weight; WG (g)-Weight gain; FC-Feed conversion; VF-Flock viability; PEI-Index of production efficiency.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In this period, an interaction (p<0.05) between factors (sex and diet) was observed in the feed intake (Table 4), with males consuming diets in greater proportion (around 9.3% more) than females. Similar results were reported by Costa et al (2001); Mendes et al (2004); Sabino et al (2004); Kolling et al (2005); Lima et al (2008); Bernal et al (2014) and Tavernari et al (2014), who, when evaluating diets with different levels of crude protein, energy and amino acids in the finisher phase, observed differences regarding sex, in which male broilers showed best performance. FI (g)-Feed intake; BW (g)-Body weight; WG (g)-Weight gain; FC-Feed conversion; VF-Flock viability; PEI-Index of production efficiency.…”
Section: Resultssupporting
confidence: 88%
“…Concerning carcass yield results (Table 5), there was no difference (p>0.05) among the factors, i.e., regardless of their diets and nutritional levels, similar behaviors were reported for males and females. Costa et al (2001); Almeida et al (2002); Mendes et al (2004); Bernal et al (2014) and Tavernari et al (2014) confirmed this result, having reported that male and female chicken carcass yields were not influenced by the nutritional levels of treatments (changes in ME, CP, and AA). Significant effects regarding carcass yield were shown by Sabino et al (2004) and Lima et al (2008), indicating that the carcass yield can improve with an increase in CP, or amino acid levels in the diet followed by average levels of energy, respectively.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Even more markedly, the experimental diet induced a reduction in BMY (−10%, P < 0.0001) and an increase in AFP (+21%, P < 0.0001) compared with the control diet, without changing LY. It has been established that Lys has a major impact on broiler carcass composition and that birds' Lys requirements for optimal BMY are greater than those based on optimal growth (Dozier et al, 2008;Bernal et al, 2014). Breast muscle in broilers serves as a protein store which is highly solicited in cases of AA deficiency (Tesseraud et al, 1999), which could explain the higher response of the breast muscle to Lys deficiency compared with other skeletal muscles.…”
Section: Resultsmentioning
confidence: 99%
“…However, according to Nascimento et al (2009), higher lysine intakes could promote higher muscle deposition and lower carcass fat accumulation, resulting in better FCR in chickens. Lower FCR for males and females broiler chickens were previously estimated at dietary lysine levels of 1.22 and 1.24%, respectively (Bernal et al, 2014).…”
Section: Resultsmentioning
confidence: 99%